Effects of two intravenouse dose levels of omeprazole on the gastric juice pH of healthy horses - Ruiz, Jhon D; Ramírez, Juan E; Lezcano, Ángel (Revista Colombiana de Ciencias Pecuarias, 2016)
omeprazole suppresses gastric acid secretion and increases gastric juice pH by blocking the H+, K+ ATPase in the secretory membrane of parietal cells. Gastric juice pH below 4, long periods of no feed intake and stress are factors predisposing to gastric ulcers in horses. Objective: to determine the effect of 1 and 2 mg/Kg intravenous (IV) omeprazole on the gastric juice pH of Colombian Creole horses. Methods: seven horses were treated with two IV levels of omeprazole (1, and 2 mg/Kg body weight (BW)) in a crossover design. The omeprazole dose for each animal was reconstituted with 100 ml 0.9% NaCl. Gastric pH was measured using a portable pH-meter in stomach samples collected at time 0 (just before treatment), and 1, 2, 3, 5, 7, 9, 11, and 24 hours post-treatment. Results: the gastric pH at time 0 fluctuated from 1.6 to 3.2 in all horses. Both omeprazole doses (1 and 2 mg/Kg) significantly increased the gastric pH (pH > 4.6) from 1 to 11 hours after the treatment. At 24 hours post-treatment, pH of the group treated with 1.0 mg/Kg significantly decreased to 2.8 ± 0.3, but remained elevated at 5.7 ± 0.87 for the group treated with 2 mg/Kg. Conclusion: the study demonstrated that a single IV omeprazole dose of 2 mg/Kg, but not 1 mg/Kg, maintained gastric pH above 4 during 24 hours.